Eventyret som lignelse: Om H.C. Andersens »De Vises Steen« - Mortensen, Klaus P. (Danske Studier, 2011)
The question of the immortality of the human soul was essential to the thinkers and poets of the golden age, including Andersen whose doubts increased with age and with the growing materialistic tendencies in theology and philosophy. He strongly rejected materialism, especially in his novel To be or not to be (1857) but also in the fairy tale »The Stone of the Wise Men« (1858). In The Story of my Life (1855) A. had claimed that the fairy tale just like the stories in the Holy Bible are not to be taken literately but as parables with a hidden meaning: an invisible thread or truth based on the unity of the beautiful, the true, and the good. The precondition for this parabolic opening of our eyes is the close cooperation of natural science (as conceived by H.C. Ørsted) and poetry. The fairy tale is thus composed as a gradual process of recognition in which the fictive persons display aspects of the futile striving for the stone of the wise men, that is: the answer to the question of immortality. But while the wisest of men and his four sons fail, his blind daughter succeeds in her unselfish efforts to save her mislead brothers because she ’sees’ with the eyes of her soul. And in that endeavour the stone of the wise men reveals itself as being the word faith. To A. with his Lutheran orientation faith is not the result of human effort but of the grace of God. In this lies the decisive difference between the siblings. While the brothers are self centered their sister is unselfish. To A., who from personal experience knew that the fear of death is closely connected with being self centered, immortality is the suspension of the individualistic focus on the ego. It is open to discussion whether the »happy end« of the fairy tale is just wishful thinking. But in that context one should consider the fact that the story teller is not part of the fictive universe but positioned outside it. Because from such an angle it is possible to consider the tale as A.s attempt to do away with his own constant and intense occupation with his self by in creating a counter image to the very source of his fear of death and oblivion.